Study of genetic parameters and relationships between agronomic and physiological traits in Kabuli type chickpea genotypes under drought stress - Hadi Afzali; Mehdi Mohayeji; Hassan Farhbakhsh (پژوهش‌های حبوبات ایران)
Introduction Chickpea is one of the most important protein producing crops in the world and drought is the greatest limiting factor for its growth. In addition, chickpea plays crucial role in soil fertility because of the nitrogen fixation in its roots. The chickpea is mostly grown in semi-arid and arid zones or in the rain fed condition. Hence, more than 90% of chickpea growing area is drought prone. Under such conditions, usually the last part of reproductive phase of chickpea, faces water deficiency. Generally terminal drought stress is responsible for reduction in yield and biomass as well as physiological traits such as CO2 assimilation, stomatal conductance, transpiration rate, membrane stability index (MSI) and water use efficiency (WUE). In this condition, stress avoidance ability, tolerance or stress escape is essential for drought resistance. Significant genetic variation exists in chickpea germplasms for terminal drought stress. Nowadays, different breeding methods used for improving chickpea drought tolerance such as Marker assisted selection, omics and mutation breeding. Besides these techniques, enough information about traits affected by drought stress, their genetic parameters and relationships with economic yield is necessary for breeding programs.